The Logistics Model Approach in Analyzing the Mobility of Migrant Work in Banjarmasin City - Syubhan Annur, Ahmad Yunani,; Adawiyah, Rabiatul (Opción)
This research is an interpretative explanatory research by analyzing primary data. Primary data collection through survey methods that are analyzed using inferential analysis (logistic regression models). The results showed that: (a) Based on logistical analysis that was proven to significantly affect the mobility of migrant residents’ work was the number of skills and wage systems. While other factors such as education, age, gender, type of previous work, and length of work were not significant. (b) The vertical pattern of job mobility that experienced an increase occurred in the trade and services sector, while the occupational mobility that experienced a decline was the agricultural sector, and the building and services sector with horizontal occupational mobility patterns.